Neurocriptococose em cães e gatos: aspectos anatomopatológicos e morfologia fúngica - Oliveira, Miguel Dewes (2023)
Cryptococcosis is a fungal infection that commonly affects dogs and cats, often manifesting with neurological signals. This study aimed to access the neuropathological characteristics of cryptococcosis in nine cats and two dogs that were necropsied at the Laboratório de Patologia Veterinária (LPV) of Universidade Federal de Santa Maria (UFSM), and using these data, it was compiled the scientific article that composes this dissertation. The methodology used included the review of the necropsy reports of cases diagnosed with cryptococcosis involving the nervous system, collecting data such as sex, breed, age, clinical signs, location of the lesions, macroscopy and histology. Histological reevaluation was performed (using hematoxylin and eosin [HE] and Alcian Blue) to characterize and locate the lesions, morphology of the agent, fungal load, type and intensity of the inflammatory infiltrate, lesions in the nervous parenchyma and morphological characteristics of the yeasts. Fungal morphological criteria, such as capsule and yeast wall thickness and budding frequency, were analyzed in each case. Only six cases presented neurological signs, with blindness and head tilt being the most common, in addition to other varied signs, such as syncope, drowsiness and ataxia. Debilitating and immunosuppressive conditions were detected in five cases. Macroscopic lesions in the central nervous system (CNS) were found in five cases, presenting as irregular, friable, soft, gelatinous and grayish masses, with distinct borders. In the sections analyzed, within the availability of paraffin blocks for reevaluation, the histological findings revealed that the telencephalic cortex was the most affected site in the CNS, observed in the 11 cases. This region exhibited a higher fungal load and lower inflammatory response, compared to other neurolocations. Among the cortical regions, the frontal cortex was involved in four cases, the parietal cortex in six and the occipital cortex in five. The cerebellum was also affected in all cases, but showed a milder inflammatory response and lower fungal burden than the telencephalic cortices. Furthermore, pulmonary involvement was also observed in all cases. The inflammatory intensity associated with yeasts in the CNS was predominantly mild to moderate, being accentuated in only two cases, and the fungal load was more frequently moderate or severe, being mild in only two cases. The heterogeneity observed in the inflammatory response and fungal burden reveals the complex nature of this infection. Other affected nervous tissues were the optic nerve and the nerve roots and ganglia of the spinal cord, mainly in cats. In conclusion, this study shows the neuropathological features of cryptococcosis in a series of cases in dogs and cats, emphasizing the importance of considering specific neurolocations in this fungal infection. In addition to contributing to a better understanding of the simultaneous involvement of the respiratory and nervous systems.